Penerapan Permodelan Nielsen Pada Website Aplikasi Inventaris Barang di Pondok Pesantren Miftahul Jannah - Sanjaya, Rudi; Jaidan Jauhari; Dedy Kurniawan (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2023)
The development of technology is increasingly fast and developing, so the need for a technology is one of the websites-based software technology, with this website being used to make difficult work easy, the purpose of this research is to design and build an inventory application for Islamic boarding schools Miftahul Jannad. in the survey village by applying the Nielsen modeling. The research method used is the method of observation, interviews and literature studies, the approach method is the Nielsen modeling method, where Nielsen's modeling consists of learnability, efficiency, memorability, few errors, satisfaction, the results of Nielsen's modeling are obtained to test the validity of learnability with counted r counts. 0.868, 0.845, 0.736, 0.619, Efficiency with r count 0.813, 0.461.0.636, 0.557, for Memorability is 0.773, 0.830, 0.814, 0.578 for memorability with the calculated r value of 0.773, 0.830, 0.814, 0.578, then for few errors obtained a value of 0.621, 0.765, 0.704, 0.653, then for satisfaction with a value of 0.732, 0.559, 0.662, 0.652, which means that with the calculated r value is more r table, where the r table is obtained 0.320, the data in the Nielsen modeling is valid, while for the reliability test it is stated that the results of the Nielsen modeling test are reliable.